2012
DOI: 10.1007/s10995-012-0974-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Preterm and Low Birth Weight Delivery by Maternal Periodontal Parameters: Receiver Operating Characteristic (ROC) Curve Analysis

Abstract: In this study we used receiver-operating characteristic (ROC) analysis to comparatively evaluate maternal periodontal parameters to predict preterm (PB) delivery and low birth weight (LBW) delivery among Jordanian women. A total of 277 pregnant women (20 weeks of gestation or less) had periodontal examination at baseline and followed up until delivery. Gestational age and birth weight were retrieved from their medical records. ROC curve analyses were used to examine the overall discriminatory power of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Indeed, it has even been suggested that periodontal disease severity may predict adverse pregnancy outcome (Al Habashneh et al. ).…”
mentioning
confidence: 99%
“…Indeed, it has even been suggested that periodontal disease severity may predict adverse pregnancy outcome (Al Habashneh et al. ).…”
mentioning
confidence: 99%
“…However, potential covariates were not accounted for in the performed analysis. Vogt et al (2010) Habashneh et al (2012) examined (at 20 weeks' gestation) and followed outcomes for 277 Jordanian women. Univariate analysis showed that women with LBW had higher levels of attachment loss, but no differences in terms of probing depths, and this was also confirmed in models accounting for a range of demographic, medical and pregnancy history variables.…”
Section: Prospective Studies Of Maternal Periodontitis and Low Birthwmentioning
confidence: 99%
“…Al Habashneh et al (2012) examined at 20 weeks' gestation 277 Jordanian women and followed their pregnancy outcomes. Univariate analysis showed that women with preterm birth had higher levels of attachment loss, but no differences in terms of probing depths, and this was confirmed in models allowing for a range of demographic, medical and pregnancy history variables.…”
Section: Case-control Studies Of Maternal Periodontitis and Preterm Bmentioning
confidence: 99%
“…More recently, Al Habashneh et al. () reported that preterm birth cases and controls differed significantly in terms of mean clinical attachment loss (CAL) and the percentage of sites with CAL ≥5 mm and ≥6 mm, but not in terms of probing depth (PD) measures or the extent of CAL at lower thresholds. Given these equivocal findings, it is not possible to identify from the existing literature a disease definition that is consistently and strongly associated with preterm birth risk and that could be used to define eligibility in future RCTs.…”
Section: Possible Explanations Why Periodontal Treatment Does Not Affmentioning
confidence: 99%